2011
DOI: 10.1002/elps.201100203
|View full text |Cite
|
Sign up to set email alerts
|

Difference gel electrophoresis identifies differentially expressed proteins in endoscopically collected pancreatic fluid

Abstract: Alterations in the pancreatic fluid proteome of individuals with chronic pancreatitis may offer insights into the development and progression of the disease. The endoscopic pancreas function test (ePFT) can safely collect large volumes of pancreatic fluid that are potentially amenable to proteomic analyses using difference gel electrophoresis (DiGE) coupled with liquid chromatography-tandem mass spectrometry (LC-MS/MS). Pancreatic fluid was collected endoscopically using the ePFT method following secretin stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…In contrast, proportionally more peptidase (protease) activity-related proteins, as well as serine peptidase inhibitor (a protease inhibitor) activity-related proteins, were identified in the ultracentrifugation-precipitated sample. These classes of proteins are of particular interest in that several proteases and protease inhibitors have been identified as potential biomarkers of chronic pancreatitis (Table 3) [8, 9]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, proportionally more peptidase (protease) activity-related proteins, as well as serine peptidase inhibitor (a protease inhibitor) activity-related proteins, were identified in the ultracentrifugation-precipitated sample. These classes of proteins are of particular interest in that several proteases and protease inhibitors have been identified as potential biomarkers of chronic pancreatitis (Table 3) [8, 9]. …”
Section: Resultsmentioning
confidence: 99%
“…In our prior studies using TCA protein precipitation, we identified several dozen potential protein biomarkers for chronic pancreatitis [8, 9]. Several of these proteins (including pancreatic enzymes (amylases, lipases, chymotrypsinogens, and carboxypeptidases), enzyme inhibitors (alpha-1-antitrypsin and alpha-1-antichymotrypsin), mucins, haptoglobin and neprilysin) were also identified in ultracentrifugation-precipitated pancreatic fluid (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation